Strategi Bauran Humas dalam Membangun Citra Positif Asosiasi Perusahaan Pialang Asuransi dan Reasuransi Indonesia - Prasetyo, Sigit; Utomo, Ichsan Widi; Emeilia, Rindana Intan (CV. ITTC INDONESIA, 2023)
The decline in insurance penetration levels in recent years has been caused by the increasing number of cases of default by life insurance companies, as well as the revocation of business licenses for the insurance broker industry by the Financial Services Authority (OJK), which has resulted in lower interest among the insurance community. This incident became an obstacle for the Association of Indonesian Insurance and Reinsurance Broker Companies (APPARINDO) in carrying out a public relations strategy to build a positive image. This research aims to find out what public relations strategies are used by APPARINDO in building a positive image of the company, and what challenges are faced when implementing the public relations strategy. The method used in this research is a qualitative descriptive method by collecting primary data through interviews from selected informants and secondary data, namely the results of documentation and direct observation. The informants in this research were the Secretariat General of APPARINDO, the Department of Public Relations and Promotion, and the Head of the Secretariat. The results show that APPARINDO implements the public relations mix strategy or PENCILS developed by Thomas L. Harris. The strategies implemented include Publications, Events, News, Community Engagement, Lobbying and Negotiations, and Social Responsibility.